Acute fatigue in endurance athletes: The association between countermovement jump variables and creatine kinase response - Yánez, C. A.; Cohen, D.; Serrato, M.; Ospina, A. L. (European Journal of Human Movement, 2023)
The purpose of this study was to determine the variables of acute neuromuscular fatigue (NMF) and its correlation with the serum concentration of creatine kinase (CK) pre- and post-training through performance analysis counter movement jump (CMJ). Methods: Eight male endurance performance athletes performed 3 trials CMJ in force platform before and after fatigue protocol high intensity intermittent running (PFAI) (fatiguing to the maximum possible rate of work for each repetition Protocol). A total of 8 variables were analyzed through CMJ and the biomarker CK before and after fatigue protocol. Results: No significant differences for the variables of mean force MF (P = 0,62. d = 0,03), time to peak force TTPF (P = 0,46. d = 0,43), jump height JH (P = 0,19. d = 0,65), flight time FT (P = 0,26. d = 0,58), relation flight time: contraction time FT: CT (P = 0,74. d = 0,59) and CK (P = 0,79. d = 0,31). Significant differences in variables of peak power (p = 0.008. d = 1,37) and contraction time (p = 0.01. d = 0,76) were found. Finally, Spearman`s correlation (Spearman`s Rho) for non-parametric tests was performed between peak power (PP) (p = 0.002) (r = 0.92) and contraction time (CT) (p = 0.001) (r = 0.97). Conclusions: There is a neuromuscular fatigue state in the acute phase determined of CMJ variables, independent of lineal relation CK production. Likewise, it is highlighted a major parameter the reduction of peak power and increment of contraction time in the neuromuscular performance.